Objective evidence for chronic back pain relief by Medical Yoga therapy - Arya, Suvercha; Yadav, Raj Kumar; Venkataraman, Srikumar; Deepak, Kishore Kumar; Bhatia, Renu (Frontiers in Pain Research, 2022)
Chronic low back pain (CLBP) is a musculoskeletal ailment that affects millions globally. The pain is disturbing with impaired motor activity, reduced flexibility, decreased productivity and strained interpersonal relationships leading to poor quality of life. Inflammatory mediators in the vicinity of nociceptors cause peripheral and central sensitization presented as hyperalgesia and/or allodynia either due to diminished descending pain inhibition or exaggerated ascending pain facilitation. Objective measurement of pain is crucial for diagnosis and management. Nociceptive flexion reflex is a reliable and objective tool for the measurement of a subject’s pain experience. Medical Yoga Therapy (MYT) has proven to relieve chronic pain, but the objective evidence-based assessment of its effects is still lacking. We objectively assessed effect of MYT on pain and quality of life in CLBP patients. We recorded VAS (Visual analogue scale), Mc Gill Pain questionnaire and WHOQOL BREF questionnaire scores, NFR response, and Diffuse noxious inhibitory control tests. Medical yoga therapy consisted of an 8-week program (4 weeks supervised and 4 weeks at home practice). CLBP patients (42.5 ± 12.6 years) were randomly allocated to MYT (n=58) and SCT groups (n=50), and comparisons between the groups and within the groups were done at baseline and at end of 4 and 8 weeks of both interventions. (VAS) scores for patients in both the groups were comparable at baseline, and subjective pain rating decreased significantly more after MYT compared to SCT (p=< 0.0001*, p= 0.005*). Mc Gill Pain questionnaire scores revealed a significant reduction in pain experience in the MYT group compared to SCT. Nociceptive Flexion Reflex threshold increased significantly in the MYT group at end of 4 weeks and 8 weeks, p< 0.0001#, p=<0.0001∞ respectively) whereas for SCT, we did not find any significant change in NFR thresholds. DNIC assessed by CPT also showed significant improvement in descending pain modulation after MYT compared to SCT both at end of 4 and 8 weeks. Quality of life also improved significantly more after MYT. Thus, we conclude with objective evidence that Medical Yoga Therapy relieves chronic low back pain, and stress and improves the quality of life better than standard care.